Endothelial invasive response in a co‐culture model with physically‐induced osteodifferentiation. (13th June 2012) - Traphagen, Samantha B; Titushkin, Igor; Sun, Shan; Wary, Kishore K; Cho, Michael
Abstract: Manipulation of stem cells using physicochemical stimuli has emerged as an important tool in regenerative medicine. While 2D substrates with tunable elasticity have been studied for control of stem cell differentiation, we recently developed a stratified co‐culture model of angiogenesis of human mesenchymal stem cells (hMSCs) that differentiate on a tunable polydimethylsiloxane (PDMS) substrate, thereby creating a physiologic context for elasticity‐induced differentiation. Endothelial cells (EC) were cultured on top of the hMSC construct on a collagen gel to monitor network formation. Media composition influenced EC invasion due to the conditioning media, the reduction of serum and supplemental growth factors, and the addition of recombinant growth factors. Conditioned media, recombinant growth factors and direct co‐culture were compared for endothelial cell invasive response using quantitative image analysis. As anticipated, use of recombinant vascular endothelial growth factor (VEGF) induced the deepest EC invasions while direct co‐culture caused shallow invasions compared to other conditions. However, endothelial cells displayed lumen‐like morphology, suggesting that cell‐cell interaction in the co‐culture model could mimic sprouting behaviour. In summary, an engineered suitable biochemical and physical environment facilitated endothelial cells to form 3D vessel structures onto hMSCs. These structures were plated on a stiff surface known to induce osteodifferentiation of stem cells. This low cost co‐culture system, with its minimal chemical supplementation and physically controllable matrix, could potentially model in vivo potential in engineered and pre‐vascularized bone grafts. Copyright © 2012 John Wiley & Sons, Ltd.